Znaczenie ekoinnowacji dla rozwoju przedsiębiorstw - Ziółkowski, Bożydar (The importance of ecoinnovations for enterprises development, 2007)
Ecoinnovations are examples of products that generate some value added combined with the lack or little influence on the environment. Because of this, their importance for enterprises is especially great. The importance will be increasing in the European Union due to the created policy of suport for ecoinnovations. Among the most important instruments created within this area for the years 2007-2013 are: Entrepreneurship and Innovation Programme and Competitiveness and Innovation Framework Programme.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 526-534